In vitro evaluation of antimicrobial effects of citrus limonum essential oil on some endodontic pathogens (Annals of Medical Research, 2022)
Aim: To investigate the antimicrobial effects of Citrus limonum and calcium hydroxide comparatively and to evaluate MIC, MBC, and MFC levels for some microorganismal strains of the root canal microbial flora.Materials and Methods: Enterococcus faecalis, Candida albicans, Staphylococcus aureus, Streptococcus mutans, and Escherichia coli standard strains were used. Microorganisms were cultivated and used for the evaluation of the antimicrobial effect of the different concentrations of the C.limonum and calcium hydroxide using disc diffusion and agar well diffusion methods. Then MIC, MBC, and MFC values were recorded.Results: Wider inhibition zones were obtained for C.limonum essential oil compared to calcium hydroxide. In the agar well diffusion method, while the widest inhibition zone was obtained for C.albicans, the narrowest inhibition zone was observed for E.faecalis for C.limonum. For calcium hydroxide, the widest inhibition zone was in C.albicans cultures, however, the narrowest inhibition zone was observed for S.mutans. In the agar disc diffusion method, the widest inhibition zone was observed for C.albicans, and the narrowest inhibition zone was spotted in S.aureus for Citrus limonum. For calcium hydroxide, while the widest inhibition zone again reached for C.albicans, the narrowest inhibition zone was found for E.faecalis. The lowest MIC and MBC value for Citrus limonum was observed in S.mutans. For calcium hydroxide, the lowest MIC and MBC values were recorded for S.aureus, E.coli, and S.mutans.Conclusion: Data in experimental conditions showed that C.limonum essential oil may be an alternative candidate, and superior to calcium hydroxide in terms of antimicrobial activity for all chosen members of intracanal flora.
Keywords: Citrus limonum; essential oil; antimicrobial effect